Correlation between Troponin T and N-Terminal Brain Natriuretic Peptide Levels and cardiac Structure and Function and Cardiovascular Disease in Elderly Maintenance Hemodialysis Patients: Troponin T and N-Terminal Brain Natriuretic Peptide Levels - Zhang, Ning; Zhang, Kaige; Xu, Xin; Hu, Jian; Wang, Xiaoqin; Meng, Xin (Cellular and Molecular Biology, 2022)
With the development of chronic kidney disease (CKD), the patients showed a gradual decline in renal function, which eventually progressed to end-stage renal disease (ESRD), accompanied by various cardiovascular and cerebrovascular events. Maintenance hemodialysis (MHD) is one of the effective methods to treat ESRD, but some patients still die from cardiovascular and cerebrovascular complications. The purpose of this study was to investigate the relationship between troponin T (TnT), n-terminal brain natriuretic peptide (NT-proBNP), cardiac structure and function and cardiovascular disease in maintenance hemodialysis patients. In this experimental study, 100 patients with MHD were randomly selected as research objects. According to the level of NT-proBNP before dialysis, they were divided into two groups, namely the low NT-proBNP group and the high NT-proBNP group. The clinical and biological indicators and the average value of echocardiography were detected in the two groups. The degree of CKD disease was divided into six stages according to GFR, and the influence of different stages on the cardiac function of CKD patients was detected. The experimental results showed that the levels of TnT and NT-proBNP in MHD patients were significantly increased, and the levels of TnT and NT-proBNP and cardiac function were correlated with the patients with cardiovascular diseases. Cardiac ultrasound confirmed that the NT-proBNP level of patients with left ventricular hypertrophy was significantly higher than that of patients without left ventricular hypertrophy, and the difference between the two was statistically significant (P<0.005).